Application Voting System of Web based in Iraq - Ameen , Zinah J. Mohammed (Iraqi Journal of Science, 2022)
Currently voting process is paper based form, by using voting card or paper; thus the counting method is done manually, which exhausts a lot of time. Obsolete votes may be possibly occurring. This paper introduced a system in which voting and counting is done with the help of computer. The election process would be easier, it saves time, avoid errors while counting and obsolete votes are reduced. Electronic voting (E-voting) system is a voting system in which the election related data is stored and handled digitally, it would become the quickest, cheapest, and the most efficient way to administer election and count vote it is considered a means to further enhance and strengthen the democratic processes in modern information societies. The suggested a web based E-voting application using ASP.net with SQL server. This application implements a voting process within a voting station and gives the election results.